An 18-month study of the effects of IBD symptomatology and emotion regulation on depressed mood - Trindade, Inês A. (2017)
Depressive symptomatology in IBD patients is known to predict disease activity, which in turn can increase depressive symptoms in a perpetuating a cycle between depression and IBD symptomatology. The mechanisms that contribute to the relationship between disease activity and depressive symptoms are not clearly investigated yet. Since emotion regulation has been considered particularly relevant to define the impact of adverse experiences on different outcomes, the current study aimed to examine the longitudinal influence of two maladaptive emotion regulation processes, cognitive fusion and brooding, on the association between disease activity and depressed mood. This study was conducted over an 18-month period, using a sample of 116 IBD patients that completed self-report validated measures in three different waves. Correlation analyses and cross-lagged panel models were performed. The main result from this study discovered that the experience of IBD symptomatology at baseline, although positively linked to the manifestation of depressed mood 18 months later (r = 0.25; p < 0.01), does not directly predict depressive symptoms. This relationship is rather indirect, as it is explained by the engagement in cognitive fusion (p = 0.028) and brooding (p = 0.017). These maladaptive emotion regulation processes, that were revealed to be consistent over time, link IBD symptoms with subsequent depressed mood. These findings indicate that clinicians should be aware of the emotion regulation processes patients tend to use to handle difficult experiences. The inclusion of psychological assessments and interventions in the healthcare of IBD patients should be seriously considered. Further implications are discussed.